2024
DOI: 10.1002/jgh3.13033
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia and frailty in inflammatory bowel disease: Emerging concepts and evidence

Pardhu B Neelam,
Alka Sharma,
Vishal Sharma

Abstract: Sarcopenia is a condition marked by progressive loss of skeletal muscle mass and function while frailty is a multidimensional concept characterized by diminished physiological reserve and increased vulnerability to stressors. Both of these were previously considered as related to aging and shown to impact the quality of life and carry prognostic significance. Emerging data show that both sarcopenia and frailty carry similar relevance in chronic illness. Inflammatory bowel disease (IBD) is characterized by chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 126 publications
(256 reference statements)
0
1
0
Order By: Relevance
“…RT can lead to an increase in IGF-1 secretion by skeletal muscle, which in turn promotes the hypertrophy of muscle fibers, enhances muscle strength, and prevents muscle loss [ 221 , 222 , 223 ]. According to recent studies, patients with Crohn’s disease who practiced RT showed significant improvements in muscle strength, muscle function, and bone mineral density [ 224 , 225 ].…”
Section: Treatmentsmentioning
confidence: 99%
“…RT can lead to an increase in IGF-1 secretion by skeletal muscle, which in turn promotes the hypertrophy of muscle fibers, enhances muscle strength, and prevents muscle loss [ 221 , 222 , 223 ]. According to recent studies, patients with Crohn’s disease who practiced RT showed significant improvements in muscle strength, muscle function, and bone mineral density [ 224 , 225 ].…”
Section: Treatmentsmentioning
confidence: 99%